Performance health administration and the return of the French second empire. Issue 2 (15th November 2017) - Simonet, Daniel
Abstract : In the French health care system, cost‐containment strategies have become the new priority. Novel instrumental values (e.g., benchmarking, incentivization or premiums, and Diagnostic‐Related Groups) and reforms of the hospital governance via the 2009 HPST Act served an austerity agenda at the expense of more patient‐centered approaches (e.g., patient choice and case management). Effecting actual changes proved more difficult than collecting data on the health system. Decision‐making powers are increasingly concentrated within the welfare elite at the expense of the medical profession. Hence, a return to the earlier French tradition of Jacobinism. Transparency has yet to be achieved.